IODP New Ventures in Exploring Scientific Targets (INVEST): Defining the New Goals of an International Drilling Program - Fumio Inagaki (Scientific Drilling, 2010)
The INVEST conference, an international meeting to define the scientific goals and required technology for a new ocean drilling program, was held at the University of Bremen on 22–25 September 2009. Based on the large attendance and vigorous engagement of scientists in the discussion of new science/technology ideas, INVEST was extremely successful. Initially 400 participants were expected, but the INVEST steering and organization committees were thrilled to see a much larger number of scientists flock to Bremen to demonstrate their support and enthusiasm for the continuation of an international scientific ocean drilling program. In all, 584 participants, including sixty-four students, from twenty-one nations and >200 institutions and agencies attended the INVEST conference. Contributions to INVEST included 103 submitted white papers that were posted on the INVEST webpage (http://www.marum.de/iodp-invest. html), and breakout discussions in fifty working groups that focused on a range of topics during the course of the conference. In addition, students and early career scientists, as well as national funding agency managers and platform providers, presented a total of eighty-six posters. Interspersed with the working group and plenary sessions were twelve keynote lectures, chosen to highlight overarching themes and new directions in research and technology.